Yersinia enterocolitica enterotoxins and their pathogenicity in rabbits* - MAHAL, J S; SINGH, AJIT; SHARMA, D K; BRAR, R S (The Indian Journal of Animal Sciences, 2013)
The ileal loop response to study enterotoxin production by 8 strains of Y. enterocolitica varied from 555 to 692 alpha l/cm), The maximum fluid accumulation was observed at 4 hr time interval. At 121Â°C for 15 min, 62.46% of enterotoxin activity was retained, hut was completely lost in 5 strains when heated for 2 min. Heat stability of enterotoxin was further confirmed by infant mouse assay. Culture Supermatants of all the strains were positive for skin permeability factor(PF)activity, Maximum PF activity was given by strain R65 (342 mm2). Marked histopathological alterations in various tissues of rabbits were observed after intravenous and intraluminal injections of enteroloxins.